Discovering the Challenges of Machine Translation from Dari Language into English Language - Mohammad Shouaib (Randwick International of Education and Linguistics Science Journal, 2022)
Machine translation involves the use of unnatural computer programs to translate from one language into another language without the involvement of human translators. It is not just about substituting words in one language for those in another. Machine translation involves the use of computational linguistic techniques to recognize and translate whole phrases while also considering the complex structure and figures of speech that are unique to each language.The current paper aims at casting a new light and exploring the problems of Machine Translator as an aid used by the students of translation to render from Dari into the English language. Also, the study aims at finding out such problems encountered by these students who study translation subject. To a achieve the objectives of the study, students who were enrolled in the translation subject in the faculty of language and literature, English department for female students during the academic year 2020/2021 who were randomly selected by the researcher. A questionnaire with multiple choices was administered. The collected data were analyzed properly. The study has come out with spectra of results among them are the followings: The students who were the sample of the study faced various types of problems such as syntactic and semantic problems while using machine translation for rendering their given tasks. The rendition of target language used in the machine translator is inaccurate. And translation some specific cultural terms through a machine translation were out of context.